(untitled) (TAMADDUN NURI JURNALI, 2024)
In our country’s history, many philanthropists have become famous for their good deeds and philanthropy. One of the leaders of the people at those times was Chorikulboy. The article tells about Chorikulboy’s merits to the people and the bridge’s history with his name, which has survived to this day.